Inclusive practice in the primary school : a route map for student teachers - Trussler, Sarah (Los Angeles, California, USA : SAGE, 2015)
This is a theoretically sound practical guide to inclusion in primary schools that provides a clear and flexible framework for effective inclusive teaching.
Understanding special education needs, disability and inclusive education -- The policy context for special education needs, disability and inclusive education -- Models of difference and differentiation -- Inclusive classroom practice -- The 'special pedagogy' debate -- Strengthening the 'whole child' approach through the spiral spectrum method -- Personal, social and emotional development -- Communication, language and literacy development -- Physical development -- Drawing it all together--how children learn and how we teach inclusively.
COED
Includes bibliographical references and index.
COECSD
Keywords: Inclusive education; Special education